Reversible interactions with para-hydrogen enhance NMR sensitivity by polarization transfer - Adams, Ralph W; Aguilar, Juan A; Atkinson, Kevin D; Cowley, Michael J; Elliott, Paul I P; Duckett, Simon B; Green, Gary G R; Khazal, Iman G; López-Serrano, Joaquín; Williamson, David C (Science (American Association for the Advancement of Science), 2009)
The sensitivity of both nuclear magnetic resonance spectroscopy and magnetic resonance imaging is very low because the detected signal strength depends on the small population difference between spin states even in high magnetic fields. Hyperpolarization methods can be used to increase this difference and thereby enhance signal strength. This has been achieved previously by incorporating the molecular spin singlet para-hydrogen into hydrogenation reaction products. We show here that a metal complex can facilitate the reversible interaction of para-hydrogen with a suitable organic substrate such that up to an 800-fold increase in proton, carbon, and nitrogen signal strengths are seen for the substrate without its hydrogenation. These polarized signals can be selectively detected when combined with methods that suppress background signals.